STRATEGI PENGEMBANGAN KELAPA BIDO (Cocos Nucifera. L) SEBAGAI KOMODITAS UNGGULAN DAERAH DESA BIDO KABUPATEN PULAU MOROTAI PROVINSI MALUKU UTARA - Nabila ., Lohor; Wenny ., Tilaar; Hengki Djemie Walangitan (Sam Ratulangi University, 2021)
This study aims to identify socio-economic problems and agronomic potential on the island of Morotai in relation to the development of Bido Coconut and develop strategies for developing Bido Coconut as an endemic plant. This research was conducted using qualitative and quantitative methods, the research time was from February to April 2021. The data collection methods were interviews, questionnaires and observation. Data analysis used correlation analysis and SWOT analysis. The stages of analysis, correlation analysis are r_xy = Correlation between variables x and y, X = (X_(i-X )) and Y = (Y_(i-Y )). SWOT analysis, namely problem identification, determination of IFAS and EFAS, grand strategy analysis. The results of this study indicate a low to high correlation value based on the results of the correlation analysis of agronomic traits. The highest correlation was between the number of bunches and the number of fruit, which was 0.588. Where the higher the number of bunches followed by the number of fruits. The correlation of these two traits is very decisive in the selection of plant parents. Furthermore, the correlation between the number of leaflets and stem diameter is negative and the height is -0.665 meaning that the greater the diameter of the stem, the reduction is followed by the reduction of leaflets or vice versa. Correlation of fruit weight and number of leaf midribs - 0.485. Correlation results show that agronomic traits have a relationship with each other, from high to low values. The results of the SWOT analysis from the SWOT analysis weight matrix, the value of x is 1.05 (total total score between strengths and weaknesses) and y value is 1.53 (total number of scores between opportunities and threats). The position of the strategy in developing Bido Coconut as a leading commodity for the Morotai Island Regency, the strategy for developing Bido Coconut as a leading commodity in the Morotai Island Regency is an aggressive strategy for quadrant 1 which is a very profitable situation. The area has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is the need to support a very aggressive growth pattern (growth oriented strategy).